Principles of Macroeconomics 2e support material for OpenStax textbook: week 2, chapter 6 - OER project materials - Miller, Ray, author; Bhattarai, Niroj, author; Nunes, Débora, author (Colorado State University. Libraries, 2023)
Week 2 discussion: Measuring GDP (chapter 6). The material included here was developed to support the use of the OpenStax textbook Principles of Macroeconomics 2e. The material includes two components: (1) weekly discussion prompts that were developed for use on online discussion boards; and (2) weekly recitation worksheets and answer keys.

Please see online textbook: https://openstax.org/details/books/principles-macroeconomics-2e.
Missing weeks are exam review weeks. There is a discussion prompt but no recitation material for week 4 (exam review).
ECON 204.
Keywords: Economics -- Study and teaching (Higher)